Ali je postopek odvzema premoženjske koristi v kazenskem postopku premalo učinkovit - Šošić, Miha (Podjetje in delo, 2016)
The author discusses the effectiveness of asset forfeiture in criminal proceedings. The effectiveness of asset forfeiture is not understood in a statistical sense, but rather in a specific legal sense. The author aims to examine the effectiveness of asset forfeiture by analysing the relevant provisions of Slovenian laws. The standard for examining the effectiveness of asset forfeiture is the specific restitutionary function of asset forfeiture as well as the protection of human rights and respect for the rule of law.
Keywords: človekove pravice; kazenski postopek; kazniva dejanja; pravna država; storilci; zaplemba premoženja